Blood-brain barrier (BBB) and the complement landscape. (October 2018) - Alexander, Jessy J.
Highlights: The blood-brain barrier is a gateway serving as first line of defense into the brain. The complement system is the first line of defense against infections. Both systems are beneficial or problematic depending on the setting. Both systems intersect and interact to maintain brain homeostasis. Abstract: The brain is an immune privileged organ, uniquely placed in the body. Two systems involved in maintaining brain homeostasis and in protecting the brain are the blood-brain barrier (BBB) and the complement system. The BBB is present in the vasculature of the brain and is the dynamic interface between brain and body that regulates what enters and leaves the brain, thereby maintaining the brain microenvironment optimal for brain function. The complement system is ubiquitous, being present systemically and in the brain, both membrane bound and in circulation. It is an important arm of the body's defense that helps maintain homeostasis by eliminating debris and damaged cells, participating in destroying pathogens, promoting inflammation and conveying 'danger signals'. Recent studies reveal that the complement system plays an important role in normal brain development. However, when the complement system is overwhelmed, complement activation could contribute to loss of BBB integrity resulting in brain pathology. Studies support an association between complement proteins and BBB dysfunction, with the mechanisms being slowly unraveled. This review will provide an overview of both these systems, how they intersect and interact with each other.